BLOCK CIPHERS ON THE BASIS OF REVERSIBLE CELLULAR AUTOMATA - Tanasyuk, Yuliya; Burdeinyi, Petro (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
The given paper is devoted to the software development of block cipher based on reversible one-dimensional cellular automata and the study of its statistical properties. The software implementation of the proposed encryption algorithm is performed in C# programming language in Visual Studio 2017. The paper presents specially designed approach for key generation. To ensure desired cryptographic stability, the shared secret parameters can be adjusted to contain information needed for creating substitution tables, defining reversible rules, and hiding final data. For the first time, it is suggested to create substitution tables based on iterations of a cellular automaton that is initialized by the key data.